The Trans-Java Toll Road as Neoliberal Spatial Fix: Economic Restructuring and MSME Marginalization - Naim, Chanif (Journal of Contemporary Sociological Issues, 2025)
This article critically examines the socio-spatial impact of the Trans-Java Toll Road on Java's northern coastal region, also known in Indonesian as Pantura, with a focus on micro, small, and medium enterprises (MSMEs). While promoted as a solution for improving logistics and economic growth, the toll road exemplifies a neoliberal spatial fix that unevenly redistributes development. Drawing on David Harvey's concepts of "spatial fix" and "uneven geographical development", this study explores how infrastructure megaprojects privilege specific spaces while displacing others. Using a critical-qualitative approach grounded in "critical realism", the research analyses curated secondary data, policy documents, statistical releases, academic studies, and news reports through hybrid thematic analysis. Findings reveal that MSMEs along the Pantura corridor face declining income, reduced visibility, and business closures, while toll-exit zones attract concentrated investment and land speculation. This spatial reordering illustrates the contradictions of capital-driven infrastructure, which deepens regional inequality and marginalizes historically embedded economies. This study argues for inclusive planning that recognizes the non-neutrality of infrastructure and prioritizes spatial justice. Furthermore, contributes to broader debates on infrastructure, dispossession, and development in post-authoritarian Indonesia and the Global South. Keywords: Displacement, Infrastructure, MSMEs, Pantura, Spatial Fix